The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nano12040673
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanotechnology: Plant-Mediated Nanoparticle Synthesis and Application

Abstract: The key pathways for synthesizing nanoparticles are physical and chemical, usually expensive and possibly hazardous to the environment. In the recent past, the evaluation of green chemistry or biological techniques for synthesizing metal nanoparticles from plant extracts has drawn the attention of many researchers. The literature on the green production of nanoparticles using various metals (i.e., gold, silver, zinc, titanium and palladium) and plant extracts is discussed in this study. The generalized mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 180 publications
1
43
0
Order By: Relevance
“…Analyses of the composition of Echinacea extracts revealed that chicoric acid was the dominant component (among the phenylpropanoids) [ 13 ], along with phenolic compounds such as flavonoids [ 14 ], tannins, alkaloids, starch, furochromones, and glycosides [ 15 ], all of them acting as reducing agents and stabilizing agents in the synthesis of nanoparticles [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the composition of Echinacea extracts revealed that chicoric acid was the dominant component (among the phenylpropanoids) [ 13 ], along with phenolic compounds such as flavonoids [ 14 ], tannins, alkaloids, starch, furochromones, and glycosides [ 15 ], all of them acting as reducing agents and stabilizing agents in the synthesis of nanoparticles [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in the process of synthesizing metal nanoparticles by reduction method, the length of reaction time will affect the synthesis amount and particle size distribution of metal nanoparticles ( Khan, et al, 2022 ). After determining the optimal reaction pH and temperature for synthesizing GO-AgNPs using GA at 9 and 45°C, in order to explore the effect of reaction time on the number and morphology of AgNPs in GO-AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely used in some catalytic reactions, [1] such as the photocatalytic production of hydrogen [2] and molecular Oxygen Promotes Hydrogen Production from formaldehyde Solution [3] . Unfortunately, agglomeration tends to occur due to the high surface energy of AgNPs [4–6] . Therefore, it is challenging to obtain uniformly distributed AgNPs materials, and a suitable carrier is usually chosen as the substrate material for AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Unfortunately, agglomeration tends to occur due to the high surface energy of AgNPs. [4][5][6] Therefore, it is challenging to obtain uniformly distributed AgNPs materials, and a suitable carrier is usually chosen as the substrate material for AgNPs.…”
Section: Introductionmentioning
confidence: 99%